Analisis Elektrik Motor Penggerak TBS (Traveling Band Screen) PLTU - Muliandhi, Puri; Sulistyo, Isya Aryan (Universitas Semarang, 2022)
The Traveling Band Screen (TBS) is a means of filtering trash and sea creatures such as jellyfish in the PLTU Intake area. FFB filters waste by rotating the screen, then the waste is sprayed using backwash water so that the filtered waste can fall into the disposal route. The amount of impurity material stuck on the screen has an impact on the decrease in flow capacity, thus affecting the increase in the load of the TBS motor and causing the TBS to become overloaded so that the PLTU will Shut Down, so an analysis is needed to determine the electric ability of the motor drive of the TBS system to block the screen. One of the analyzes carried out is observing the optimal load of the motor with power: 2/1 HP, Rotation: 1500 rpm with reduction ratio: 1500: 1 to determine the load blockage by using the SEW Eurodrive motor manufacturer. From the results of the load analysis, the existing motor specifications are only able to operate for a screen clogging percentage of less than 13.6%.